Governmental Illegitimacy and Incompetency in Canada and Other Liberal Nations: Implications for Health. (January 2019) - Raphael, Dennis; Komakech, Morris; Bryant, Toba; Torrence, Ryan
The welfare state literature on developing nations is concerned with how governmental illegitimacy and incompetency are the sources of inequality, exploitation, exclusion, and domination of significant proportions of their citizenry. These dimensions clearly contribute to the problematic health outcomes in these nations. In contrast, developed nations are assumed to grapple with less contentious issues of stratification, decommodification, and the relative role of the state, market, and family in providing economic and social security, also important pathways to health. There is an explicit assumption that governing authorities in developed nations are legitimate and competent such that their citizens are not systematically subjected to inequality, exploitation, exclusion, and domination by elites. In this article, we argue that these concepts should also be the focus of welfare state analysis in developed liberal welfare states such as Canada. Such an analysis would expose how public policy is increasingly being made in the service of powerful economic elites rather than the majority, thereby threatening health. It would also serve to identify means of responding to these developments.